Mechanistic understanding of rapid gelation of silk fibroin using a biosurfactant – sophorolipid - Dubey, Parul; Nawale, Laxman; Sarkar, Dhiman; Nisal, Anuya; Prabhune, Asmita (National Science Day, At CSIR-NCL, 2015)
3D polymeric hydrogels find use in biomedical applications as scaffolds and drug delivery vehicle • Silk fibroin a structural protein is a promising candidate (excellent thermo-mechanicals, biocompatibility, biodegradability) • Sophorolipid (SL)-a biosurfactant is known to exhibit antimicrobial, anti cancerous and cell differentiating. • Use of SL as gelling agent can enhance the applicability of SF hydrogels • SF-SL scaffolds obtained by lyophilization of hydrogels can find application in tissue regeneration

Mechanism of adhesion of natural polymer coatings to chemically modified siloxane polymer - Joseph, Emmanuel; Rajput, Shatruhan Singh; Patil, Shivprasad; Nisal, Anuya (Langmuir, 2021)
Surface coatings play an important role in improving the performance of biomedical implants. Polydimethylsiloxane (PDMS) is a commonly used material for biomedical implants, and surface-coated PDMS implants frequently face problems such as delamination or cracking of the coating. In this work, we have measured the performance of nano-coatings of the biocompatible protein polymer silk fibroin (SF) on pristine as well as modified PDMS surfaces. The PDMS surfaces have been modified using oxygen plasma treatment and 3-amino-propyltriethoxy-silane (APTES) treatment. Although these techniques of PDMS modification have been known, their effects on adhesion of SF nano-coatings have not been studied. Interestingly, testing of the coated samples using a bulk technique such as tensile and bending deformation showed that the SF nano-coating exhibits improved crack resistance when the PDMS surface has been modified using APTES treatment as compared to an oxygen plasma treatment. These results were validated at the microscopic and mesoscopic length scales through nano-scratch and nano-indentation measurements. Further, we developed a unique method using modified atomic force microscopy to measure the adhesive energy between treated PDMS surfaces and SF molecules. These measurements indicated that the adhesive strength of PDMS-APTES-SF is 10 times more compared to PDMS-O-2-SF due to the higher number of molecular linkages formed in this nanoscale contact. This lower number of molecular linkages in the PDMS-O-2 indicates that only fewer numbers of surface hydroxyl groups interact with the SF protein through secondary interactions such as hydrogen bonding. On the other hand, a larger number of amine groups present on PDMS-APTES surface hydrogen bond with the polar amino acids present on the silk fibroin protein chain, resulting in better adhesion. Thus, APTES modification to the PDMS substrate results in improved adhesion of nano-coating to the substrate and enhances the delamination and crack resistance of the nano-coatings.

Myristic acid derived sophorolipid: efficient synthesis and enhanced antibacterial activity - Abhyankar, Isha; Sevi, Ganesh; Prabhune, Asmita A.; Nisal, Anuya; Bayatigeri, Santhakumari (ACS Omega, 2021)
Microbial glycolipids are one of the most interesting alternatives to chemical-based surfactants as they exhibit improved biodegradability and less toxicity. However, their potential has been limited because of specificity of the yeast toward fatty acids having a carbon 16 or carbon 18 chain. This study focuses on sophorolipid (SL) production by the yeast Starmerella bombicola using myristic acid, a medium-chain carbon-14 fatty acid that has not been used as a substrate for SL production. The production was optimized for inoculum size and lipophilic substrate concentration. Furthermore, we also studied the effect of medium-chain fatty acid on yeast cell growth and optimized the process for excellent yield. The myristic acid SL (MASL) so synthesized consisted of mono- and diacetylated forms with preferential glycosylation at the methyl end group, as determined by high-resolution mass spectrometry. Individual congeners of the crude mixture were separated using dry column chromatography and then structurally characterized by mass spectrometry. The synthesized MASL was also shown to have promising surface tension, lowering abilities with a low CMC of 14 mg/L. The SL derived from myristic acid exhibited superior antibacterial activity as compared to SL derived from oleic acid. MASL was also found to be more potent against Gram-positive organisms as compared to Gram-negative organisms. This work, therefore, demonstrates successful synthesis of myristic acid-derived SL and its superior antibacterial activity, establishing a promising future for this biosurfactant.